2016
DOI: 10.1016/j.cherd.2015.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Microcarriers’ suspension and flow dynamics in orbitally shaken bioreactors

Abstract: In the present work an effort is made to determine the suspension speed of microcarriers in an orbitally shaken bioreactor of cylindrical geometry, and to assess the associated two-phase flow by means of Particle Image Velocimetry (PIV). Microcarrier technologies are commonly used in the bioprocess industry to culture adherent-dependent cells in three dimensional flow. Commercial GE Cytodex microcarriers were employed throughout this study to best mimic the flow conditions occurring in a bioreactor under stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“… for larger reactors ( d i = 10–125 cm) indicated that the Froude number ratio, Fr / Fr cr , is an effective scaling parameter for mixing time measurements in shaken cylinders under a wide range of operating conditions. The flow transition identified by the Froude number ratio was also found to accurately predict the full suspension speed of microcarriers across different bioreactor geometries (cylindrical vessels and flasks) and scales , . The two‐phase PIV study of Pieralisi et al.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“… for larger reactors ( d i = 10–125 cm) indicated that the Froude number ratio, Fr / Fr cr , is an effective scaling parameter for mixing time measurements in shaken cylinders under a wide range of operating conditions. The flow transition identified by the Froude number ratio was also found to accurately predict the full suspension speed of microcarriers across different bioreactor geometries (cylindrical vessels and flasks) and scales , . The two‐phase PIV study of Pieralisi et al.…”
Section: Introductionmentioning
confidence: 86%
“…The two‐phase PIV study of Pieralisi et al. demonstrated that the flow dynamics in the presence of GE Cytodex 3 microcarriers (∼400 μm after swelling) is only marginally affected by the solid phase with minimal slip velocity (≈ 0.02 πNd o ).…”
Section: Introductionmentioning
confidence: 99%
“…In these preliminary studies, we sought to investigate whether mixing could enhance cell proliferation on the microspheres compared to static culture. In this work a microwell plate format reported, corresponding to a critical Froude number at which the transition occurs, and the analysis has been extended to two-phase flows in the presence of microcarriers 26 . While their work has been carried out using a well internal diameter d i = 10 cm (larger than the one employed in this study), the equations can be applied in first approximation to smaller systems to be able to calculate the critical speed at which transition occurs and predict the flow pattern inside the well.…”
Section: Introductionmentioning
confidence: 99%
“…Rodriguez et al . and Pieralisi et al . designed orbital shaking bioreactors with conical bottoms aimed at maximizing microcarriers suspension, and their research showed that lower shaking frequency was required to achieve similar flow dynamics conditions in contrast with flat bottom bioreactors.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 11 and Liu et al 12 quantitatively investigated the key parameters of shake flasks and reported the advantages of efficient mass transfer and a distinctive shear property in baffled flasks compared with unbaffled flasks. Rodriguez et al 13 and Pieralisi et al 14 designed orbital shaking bioreactors with conical bottoms aimed at maximizing microcarriers suspension, and their research showed that lower shaking frequency was required to achieve similar flow dynamics conditions in contrast with flat bottom bioreactors.…”
Section: Introductionmentioning
confidence: 99%